Dyslipidemic Diet Induces Mobilization of Peripheral Neutrophils and Monocytes That Exacerbate Hemorrhagic Brain Injury and Neuroinflammation - Li, Xiuping; Cheng, Xiaojing; Wang, Xuejiao; Liu, Qiang; Ma, Hongshan; Li, Minshu (Frontiers in Cellular Neuroscience, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) is a common liver condition characterized by a significant accumulation of lipids in the liver without excessive alcohol consumption. Accumulating evidence suggests a significantly increased risk of intracerebral hemorrhage (ICH) in NAFLD patients. However, it remains poorly understood whether and how NAFLD affects the outcome of hemorrhagic brain injury. Here, we examined the effects of diet-induce NAFLD on ICH injury and neuroinflammation in mice. Methods: NAFLD was induced in C57BL/6 mice by feeding with a methionine-choline deficient (MCD) diet for 4 weeks. Collagenase and autologous blood models were used to evaluate the effects of NAFLD on ICH injury and neuroinflammation. Results: MCD diet for 4 weeks induces NAFLD and hyperlipidemia in mice. Mice receiving the MCD diet have aggravated neurological deficits and brain edema after ICH. The augmentation of ICH injury was accompanied by brain infiltration of neutrophils and monocytes and increased production of pro-inflammatory factors. Before ICH, MCD diet-induced mobilization of neutrophils and monocytes in the periphery. Notably, the detrimental effects of NAFLD on ICH injury was ablated in mice receiving antibody depletion of neutrophils and monocytes. Conclusions: These results suggest that NAFLD exacerbates neuroinflammation and ICH injury.